Tension pneumoperitoneum: case report of a rare form of acute abdominal compartment syndrome (2019)
Introduction: Tension pneumoperitoneum is a severe and rare form of pneumoperitoneum with concomitant hemodynamic instability and respiratory failure. It is a variant of abdominal compartment syndrome (ACS) causing an abrupt increase in intra-abdominal pressure. Presentation of case: We present a case of pneumoperitoneum, after an endoscopic mucosal resection with the development of ACS. The patient was successfully treated with percutaneous decompression. Discussion: Decompressive laparotomy is the first treatment option for both most forms of pneumoperitoneum and ACS; nevertheless, this issue is controversial. Recent reports have shown that some patients may be candidates for a minimally invasive catheter decompression avoiding major decompressive surgery. Identifying these patients is vital to avoiding unnecessary surgeries. Conclusions: Tension pneumoperitoneum is a life-threatening event, early detection and intervention is critical in order to provide prompt and optimal treatment approaches.